Pharmacogenetic-Guided Algorithm to Improve Daily Dose of Warfarin in Elder Han-Chinese Population - Ren, Yirong; Yang, Chenguang; Chen, Hao; Dai, Dapeng; Wang, Yan; Zhu, Huolan; Wang, Fang (Frontiers in Pharmacology, 2020)
Objective To verify the accuracy of the International Warfarin Pharmacogenetics Consortium (IWPC)algorithm, identify the effects of genetic and clinical factors on warfarin stable dose, and to establish a new warfarin stable dose predictionalgorithm for the elderly Han-Chinese population under the guidance of pharmacogenetics. Methods According to the inclusion criteria, 544 patients with non-valvular atrial fibrillation who were receiving warfarin anticoagulation therapy were enrolled. The data of the whole population, people under 65 years old and over 65 years old were respectively substituted into the IWPC algorithm to verify its accuracy. The basic data and clinical information of 360 elderly people were collected for statistical treatment, and the genotypes of VKORC1-G1639A and CYP2C9 were detected by polymerase chain reaction (PCR). The new elder pharmacogenetics warfarin dosing algorithm is obtained by stepwise multiple linear regression. The root mean squared error (RMSE) , determination coefficient (R2) and the proportion of the predicted value within the true value range of ±20%(20%-p) were used to evaluate the accuracy of the IWPC algorithm and our new algorithm. Results Among the three different age groups, the warfarin stable dose predictive accuracy of IWPC algorithm was the lowest in the patients above 65-year-old. In the 360 patients above 65 years, the warfarin stable dose of patients carried CYP2C9 (*1*2 or *1*3) andVKORC1 (GA or GG) is significantly lower than those carried other genotype combination (2.00±0.00 mg/d, P < 0.001). We established a new elder warfarin dosing algorithm(R2=0.3714) containing height, creatinine, amiodarone usage, CYP2C9 (*1*2 or *1*3) and VKORC1 (GA or GG) genotypes. The prediction accuracy of our new algorithm was significantly better than that of the IWPC algorithm verified by RMSE, R2 and (20%-p) methods. Conclusions Polymorphisms of VKORC1 and CYP2C9 obviously affected warfarin stable dose of the elder. Combination of pharmacogenetic data along with clinical factors would help to better improve warfarin doses in the elder Han-Chinese population.